Calonectria (Cylindrocladium) Leaf Spot of Palm - Jiaming Yu; Monica L. Elliott (EDIS)
Calonectria is a fungus that affects a large number of hosts worldwide, including timber and ornamental, agricultural, and horticultural crops, causing a wide range of disease symptoms, such as cutting rot, damping-off of seedlings, leaf spot, shoot blight, and root rot. This 4-page fact sheet was written by Jiaming Yu and Monica L. Elliott, and published by the UF Department of Plant Pathology, January 2013.